Social Modalities of Kiai in The Development of Islamic Boarding School - Azizah, Nur; Sugiono, Sugiono (Journal of Educational Management Research, 2025)
This study focuses on the role of social modality of kiai in the development of pesantren institutions, with a case study at Burhanul Abrar Islamic Boarding School, Situbondo. Through a qualitative approach and case study strategy, this study explores how community trust in kiai, alumni loyalty, and kiai involvement in socio-religious forums contribute to the sustainability and strengthening of pesantren institutions. The results of the study indicate that non-material social capital such as social networks, reciprocity values, and collective norms can be effectively mobilized by kiai to encourage collective participation and social transformation based on local wisdom. The implications of these findings enrich the literature on social capital in the context of traditional religious education and highlight the importance of the kiai's position as an agent of social change in the community. This study also opens up space for new methodological approaches in the study of pesantren, while encouraging the need for further exploration with a mixed methods approach and wider coverage for more representative results.